The Perspective of FBS Students on 21st Century Skills in Universitas Negeri Medan - Nailah, Nailah; Manullang, Jessica Paskah Elizabeth; Pelawi, Faujiah Br S; Fiarnanda, Dara Siti Zahirah; Meisuri (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
The 21st century is characterized by rapid technological advancements and globalization, demanding new skills for individuals to thrive in an ever-changing world. This study explores the perspectives of students at the Faculty of Languages and Arts (FBS) at Universitas Negeri Medan regarding their preparedness and familiarity with 21st century skills, which include critical thinking, collaboration, digital literacy, and adaptability. A descriptive qualitative research methodology was employed, using a structured questionnaire to gather students' insights on their readiness to apply these skills. Results indicate that the majority of students understand the importance of these skills and feel confident in their ability to apply them, particularly in critical thinking, problem-solving, and collaborative work. The findings also highlight the students' adeptness in using technology for learning, communication, and research, demonstrating strong digital literacy. However, challenges remain in evaluating the credibility of online information. Overall, the study shows that FBS students are prepared to navigate the demands of the 21st century, utilizing critical thinking, collaboration, and digital literacy to adapt to the evolving technological landscape. This study underscores the importance of integrating 21st century skills into education to ensure students are equipped for future challenges.